Basic Study of 3 mm Dose Equivalent Measurement Technique Using the Stacked Thermoluminescent Dosimeter Method - Fujiwara, Hinata; Negishi, Toru; Takahashi, Leo; Shinsho, Kiyomitsu (Sensors and Materials, 2025)
Japan revised the dose limit for the lens of the eye in 2021 to 20 mSv/year on a five-year average, with a maximum of 50 mSv/year in any one year. This represents a significant reduction from the previous limit of 150 mSv/year and necessitates accurate measurements of the 3 mm dose equivalent. Current dosimeters, such as DOSIRIS, EYE-D™, and Vision Badge, lack the ability to provide incident photon energy information, which potentially leads to the overestimation of the actual dose to the eye lens, especially in low-energy photon environments. In this study, we investigate a method of estimating the incident photon energy using a novel stacked thermoluminescent dosimeter (TLD) arrangement. BeO and Al2O3 phosphors were stacked and the absorbed dose ratios were measured to estimate the effective energy of incident photons. The results showed that the stacked TLD method can accurately estimate photon energies in the range of 26–87 keV, which makes this a promising approach to improve dosimetry accuracy for healthcare workers exposed to ionizing radiation. The detection limits for BeO and Al2O3 were also determined to be 2.49 and 3.35 μGy, respectively. This technique has potential as a new method for lens dosimetry to provide more accurate exposure assessments for occupational radiation safety.